PENGHITUNGAN KERUGIAN KEUANGAN NEGARA OLEH KANTOR AKUNTAN PUBLIK DALAM PERKARA TINDAK PIDANA KORUPSI (Studi : Putusan Pengadilan Tipikor Pada Pengadilan Negeri Medan No. 93/Pid.Sus-TPK/2016/PN.Mdn., tertanggal 16 Februari 2017) - Muhammad Isnayanda; Alvi Syahrin; Madiasa Ablisar; Muhammad Ekaputra (Universitas Sumatera Utara, 2018)
ABSTRACT The case of corruption is a major problem in Indonesia that causes a huge loss of state and affects the decline in the quality of people's lives to disrupt economic stability. In the case of corruption (hereinafter called